The Design of Engaging Videos to Promote Luoyang Agricultural Products on Social Media Platforms - Zhang, Wenbo; Youngmee, Kotchaphan (Rajapark Journal, 2024)
This research explored the design and development of video content aimed at addressing marketing challenges and expanding sales channels for Luoyang community agricultural products on social media. The objectives were 1) to develop video content designed to promote LuoYang community agricultural products on social media platforms, 2) to evaluate the quality of video content for LuoYang community agricultural products on social media platforms, 3) to assess the performance of video content for LuoYang community agricultural products on social media platforms, and 4) to assess the satisfaction of video content for LuoYang community agricultural products on social media platforms. The study involved two sample groups: 1) 2,000 respondents who provided feedback on essential video content components, and 2) 400 viewers who evaluated the final video. Taro Yamane’s formula was applied to determine sample size with a 0.05 margin of error at a 95% confidence level. The research tools included a questionnaire on video content impact, the designed video content, quality assessments, awareness, and satisfaction evaluations. Descriptive statistics such as frequency, percentage, and standard deviation were used for data analysis. The findings identified seven key components that impact purchase decisions: 1) credibility and transparency, 2) clarity of product information, 3) engagement strategies including calls to action and influencer endorsements, 4) high-quality visual and audio elements with effective storytelling, 5) professionalism in a community-oriented narrative, 6) prioritization of credibility and detailed information, and 7) strong visuals integrated with community-focused storytelling. The video’s quality received high ratings, particularly in sound, pacing, and technical execution. Viewer awareness of Luoyang agricultural products was high, with the video effectively communicating the unique characteristics and value of these products. Social media distribution enhanced product recognition and engagement, while viewers reported high satisfaction, especially with visual and audio quality, creativity, and the video’s capacity to showcase the distinct appeal of Luoyang’s agricultural products, bolstering both confidence and interest. This study contributes to the field by providing insights into the integration of visual storytelling and interactive media, offering practical strategies for promoting community-based agricultural products and enhancing rural economic resilience.